Implementation Of Risk Management Strategies And Its Implications On Financial Performance At The Financial And Asset Office Of South Sulawesi Province - Dian Putri Amalia; Ismail Badollahi; Abdul Salam (International Journal of Economic Research and Financial Accounting, 2025)
This study aims to examine the implementation of risk management systems and their impact on financial performance at the Office of Financial and Asset Management of South Sulawesi Province. The research focuses on evaluating the effectiveness of risk management strategies in enhancing the overall efficiency, stability, and accountability of regional finances. A qualitative descriptive approach was employed, concentrating on the implementation of risk management and its effect on financial performance. Data were collected through interviews, observations, and documentation. Data analysis used the Miles and Huberman model, including data collection, reduction, presentation, and conclusion drawing to understand the phenomenon in depth. The results show that the implementation of risk management strategies at the Office of Financial and Asset Management of South Sulawesi Province has a positive impact on financial performance. Through a structured and sustainable risk control system, fiscal stability, accountability, and financial management efficiency were achieved, supporting optimal regional development and public service delivery